Performance management - Cadwell, Charles M. (American Management Association, 2000)
Organizational success depends on the continuous improvement of staff performance at al levels. People constitute the real competitive advantage in business and industries of all types. Enhancing the performance of your people and ultimately your organization depends on the continuous improvement of staff at all levels. An effective Performance Management system is essential to help employees perform at their best and align their contributions with the goals, values, and initiatives of the organization. Performance Management presents managers and supervisors with a clear model they can follow.